ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT DI TRANS BAKAL BUAH KOTA SUBULUSSALAM - Bagio Bagio; Sri Handayani; Aswin Nasution; Zulkarnain Zulkarnain (Universitas Teuku Umar, 2020)
The city of Subulussalam is one of the destinations for the transmigration program, which started in 1982. The transmigration area was the first area to cultivate palm oil farming around 1995. Palm oil farming was selected as the primary commodity cultivated on land owned by farmers. Until now, the transmigration community is still dependent on the Palm Oil commodity. With the development of the times, and the increased community needs, the age of palm oil has reached 21 to 23 years. The purpose of this study is to determine whether palm oil farmers had received a decent farming income, as well as how much land does a farmer must own to achieve economic profitability. The research method uses an income analysis and the Break Even Point (BEP) approach. The results show that the income of palm oil farmers is still feasible, as seen from the average income of Rp. 1,220,983.84 per month. While the BEP for production and the selling price of FFB is still above the value of the BEP. Furthermore, the BEP for the land area is 1.01 ha, meanwhile, in Trans Bakal Buah, the average palm oil farmer has 1.93 ha of land.Keywords: BEP Land Area, Palm Oil, Income.